2016
DOI: 10.1002/ps.4435
|View full text |Cite
|
Sign up to set email alerts
|

A negative association between bromadiolone exposure and nestling body condition in common kestrels: management implications for vole outbreaks

Abstract: The use of bromadiolone was detectable in the blood of alive non-target species. Detected bromadiolone in blood may reduce the body condition of nestlings, potentially reducing their fitness. The source of bromadiolone found in nestlings needs to be determined in future studies to derive accurate management advice. However, we urge the discontinuation of official SGAR distribution to farmers and their use in agrarian lands to minimise damage of voles on crops, particularly where common kestrels breed, and enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Thus, the study of the dispersal between nest-boxes, as conducted in other studies [ 47 , 54 ], would not be very informative in our case. We are confident in the reliability of our survival estimation, as we did not find any individuals breeding in the surroundings of our study area or any dispersing chicks breeding in any of the nearby nest-box populations (Villalar de los Comuneros– 112 km from our study area; San Martín de Valderaduey– 155 km from our study area) that we also study [ 58 , 59 ]. Nevertheless, for our purposes, natal dispersal is considered a cost in terms of fitness reduction, as it increases mortality [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the study of the dispersal between nest-boxes, as conducted in other studies [ 47 , 54 ], would not be very informative in our case. We are confident in the reliability of our survival estimation, as we did not find any individuals breeding in the surroundings of our study area or any dispersing chicks breeding in any of the nearby nest-box populations (Villalar de los Comuneros– 112 km from our study area; San Martín de Valderaduey– 155 km from our study area) that we also study [ 58 , 59 ]. Nevertheless, for our purposes, natal dispersal is considered a cost in terms of fitness reduction, as it increases mortality [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 97%
“…The dogs did not display any clinical effects of their subtoxic AR concentrations in the months after exposure. Previous studies have detected reduced body condition of wildlife with sublethal ARs concentrations [29][30][31]. In addition, subtoxic ARs levels are suspected to increase susceptibility to pathogens, while others have not found such association [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are disadvantages in using these compounds including environmental persistence and resistance. The former was demonstrated by Martínez‐Padilla et al who revealed the presence of residues of the common anticoagulant active ingredient, bromadiolone, in nestlings of common kestrels ( Falco tinnunculus ). The latter was validated by Goulois et al in house mice ( Mus musculus ), where anticoagulant efficiency is severely hampered for some anticoagulant compounds by an introgressed mutation acquired from the Algerian mouse ( Mus spretus ).…”
mentioning
confidence: 92%